2020
DOI: 10.1016/j.bbih.2020.100154
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody-associated psychiatric symptoms and syndromes in adults: A narrative review and proposed diagnostic approach

Abstract: Background Autoimmune-mediated encephalitis is a disease that often encompasses psychiatric symptoms as its first clinical manifestation’s predominant and isolated characteristic. Novel guidelines even distinguish autoimmune psychosis from autoimmune encephalitis. The aim of this review is thus to explore whether a wide range of psychiatric symptoms and syndromes are associated or correlate with autoantibodies. Methods We conducted a PubMed search to identify appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 120 publications
1
87
0
5
Order By: Relevance
“…Progressive leukoencephalopathy in white matter was found to be compatible with demyelination or inflammation defining a possible autoimmune encephalitis, but that does not fulfill the criteria defining a definitive limbic encephalitis, which requires such alterations restricted to the medial temporal lobe [ 21 ]. In a recent position paper we emphasized that an autoimmune etiology of psychiatric syndromes including cognitive impairment is conceivable [ 22 ] despite not fulfilling the criteria for autoimmune encephalitis [ 23 ]. Current consensus articles addressing how to specify a definitive limbic encephalitis reported that at least four criteria must be met (namely, a typical subacute onset of clinical symptoms, the aforementioned bilateral MRI abnormalities, and an abnormal EEG or pathological CSF parameters and careful exclusion of alternative causes) [ 21 , 23 , 24 ] in combination with the detection of now-established antibodies against neural surface antigens or onconeural antibodies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Progressive leukoencephalopathy in white matter was found to be compatible with demyelination or inflammation defining a possible autoimmune encephalitis, but that does not fulfill the criteria defining a definitive limbic encephalitis, which requires such alterations restricted to the medial temporal lobe [ 21 ]. In a recent position paper we emphasized that an autoimmune etiology of psychiatric syndromes including cognitive impairment is conceivable [ 22 ] despite not fulfilling the criteria for autoimmune encephalitis [ 23 ]. Current consensus articles addressing how to specify a definitive limbic encephalitis reported that at least four criteria must be met (namely, a typical subacute onset of clinical symptoms, the aforementioned bilateral MRI abnormalities, and an abnormal EEG or pathological CSF parameters and careful exclusion of alternative causes) [ 21 , 23 , 24 ] in combination with the detection of now-established antibodies against neural surface antigens or onconeural antibodies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The atypical presentation of progressive and fluctuating cognitive impairments in conjunction with hypoesthesia, thermohypoesthesia and dysphagia, and the patient’s tumor history prompted us to take a diagnostic approach seeking potential autoimmunity in the second patient’s course, as did recently published criteria [ 22 ]. Indeed, in patient 2 we discovered KCNA2 autoantibodies corroborated by repeated measurements, and, as in patient 1, patient 2’s antibodies were restricted to serum probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a psychiatric syndrome is detected and autoimmune encephalitis is diagnosed, this disease entity should be called autoimmune encephalitis as the cause is an encephalitis in its nature, although its presentation may be purely psychiatric. However, if a psychiatric syndrome dominates and no specific criteria of possible or probable autoimmune encephalitis are fulfilled, then any psychiatric syndrome's autoimmune basis must be subjected to further investigations, such as a recent diagnostic approach ( 3 ) that has relevance for the later application of immunotherapy. We recently developed criteria ( 3 ) by which such a psychiatric syndrome can be classified as having an probable or definitive autoimmune basis.…”
Section: Introductionmentioning
confidence: 99%
“…However, if a psychiatric syndrome dominates and no specific criteria of possible or probable autoimmune encephalitis are fulfilled, then any psychiatric syndrome's autoimmune basis must be subjected to further investigations, such as a recent diagnostic approach ( 3 ) that has relevance for the later application of immunotherapy. We recently developed criteria ( 3 ) by which such a psychiatric syndrome can be classified as having an probable or definitive autoimmune basis. A probable autoimmune origin can be assumed if patients present with a subacute (≤ 3 months) or chronic (≥ 3 months) psychiatric syndrome affecting different symptom clusters such as altered consciousness, disorientation, confusion, memory impairment, obsessive-compulsive behavior, psychosis, catatonia, mood dysfunction, anxiety, behavioral abnormalities (autism, hyperkinetic) and/or sleeping dysfunction.…”
Section: Introductionmentioning
confidence: 99%